Pengaruh Hutang Jangka Pendek Dan Hutang Jangka Panjang Terhadap Return On Asset (ROA). Pada PT.Asahimas Flat Glass,Tbk - Dzulfadeln, Prawira Aditya; Tendean, Andi; Palu, Susana Yunita (STIM-LPI Makassar, 2024)
This research aims to determine the effect of short-term debt and long-term debt on Return On Assets (ROA) at Pt.Asahimas Flat Glass, Tbk. The type of data used is qualitative data and quantitative data, the data source used is secondary data. The analytical method used is multiple linear regression. The results of the research that has been carried out have obtained an R2 value of 24.5% and an R value of 0.494. From the results of this research, t-test results were also obtained, where t-count1 < t-table value (0.4905 < 3.182), meaning that partial short-term debt has no significant effect on Return On Assets (ROA). Meanwhile, the results of the t test on long-term debt are tcount2 < t-table value (0.14 < 3.182). This means that partially long-term debt has no significant influence on Return On Assets (ROA) at Pt.Asahimas Flat Glass, Tbk. Meanwhile, the results of the f test obtained f-count < f-table with a value of (0.32 < 19.00), meaning that short-term debt and long-term debt have no effect on Return On Assets (ROA) at Pt. Asahimas Flat Glass, Tbk